2019
DOI: 10.1111/1462-2920.14805
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of parasitic infection and gut bacterial communities in bumble bees

Abstract: Summary High temperatures (e.g., fever) and gut microbiota can both influence host resistance to infection. However, effects of temperature‐driven changes in gut microbiota on resistance to parasites remain unexplored. We examined the temperature dependence of infection and gut bacterial communities in bumble bees infected with the trypanosomatid parasite Crithidia bombi. Infection intensity decreased by over 80% between 21 and 37°C. Temperatures of peak infection were lower than predicted based on parasite gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 128 publications
0
36
0
Order By: Relevance
“…The cell suspension was then mixed with an equal quantity of 4 m m ( C. mellificae ) or 16 m m ( L. passim and C. bombi ) aqueous sucralose (trade name ‘Splenda’, Heartland Food Products, UK) water for a final concentration of 1000 parasites μ L −1 . The sucralose solution was used to provide a sweet taste that encouraged consumption without the osmotic stress of a high-sugar solution (Palmer-Young et al ., 2019 a , 2019 b ), which can kill trypanosomatid cells (Cisarovsky and Schmid-Hempel, 2014); we observed that cells rapidly became deformed and immotile in 50% sugar water. The higher 16 m m sucralose concentration (8 m m in final inoculum) was used in the final 2 weeks of the experiment after this concentration was found to promote consumption.…”
Section: Methodsmentioning
confidence: 66%
See 4 more Smart Citations
“…The cell suspension was then mixed with an equal quantity of 4 m m ( C. mellificae ) or 16 m m ( L. passim and C. bombi ) aqueous sucralose (trade name ‘Splenda’, Heartland Food Products, UK) water for a final concentration of 1000 parasites μ L −1 . The sucralose solution was used to provide a sweet taste that encouraged consumption without the osmotic stress of a high-sugar solution (Palmer-Young et al ., 2019 a , 2019 b ), which can kill trypanosomatid cells (Cisarovsky and Schmid-Hempel, 2014); we observed that cells rapidly became deformed and immotile in 50% sugar water. The higher 16 m m sucralose concentration (8 m m in final inoculum) was used in the final 2 weeks of the experiment after this concentration was found to promote consumption.…”
Section: Methodsmentioning
confidence: 66%
“…Bombus impatiens and A. mellifera are both corbiculate (‘pollen-basket’) bees within the family Apidae, and both harbour a socially transmitted, phylogenetically similar gut microbiota (Kwong et al ., 2017) that is a key mediator of trypanosomatid infection in the Bombus spp./ Crithidia spp. system (Koch and Schmid-Hempel, 2011, 2012; Mockler et al ., 2018; Palmer-Young et al ., 2019 a , 2019 b ). In contrast, solitary bees – as well as the facultatively eusocial Halictids – lack the socially transmitted core gut microbiota that is a feature of B. impatiens and A. mellifera (McFrederick et al ., 2012, 2014, 2016; Kwong et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations